Anti-tumor effects and potential therapeutic response biomarkers in α-emitting meta-(211)At-astato-benzylguanidine therapy for malignant pheochromocytoma explored by RNA-sequencing - Ohshima, Yasuhiro (Theranostics, 2019)
Targeted α-particle therapy is a promising option for patients with malignant pheochromocytoma. Recent observations regarding meta-(211)At-astato-benzylguanidine ((211)At-MABG) in a pheochromocytoma mouse model showed a strong anti-tumor effect, though the molecular mechanism remains elusive. Here, we present the first comprehensive RNA-sequencing (RNA-seq) data for pheochromocytoma cells based on in vitro (211)At-MABG administration experiments. Key genes and pathways in the tumor α-particle radiation response are also examined to obtain potential response biomarkers. Methods: We evaluated genome-wide transcriptional alterations in the rat pheochromocytoma cell line PC12 at 3, 6, and 12 h after (211)At-MABG treatment; a control experiment using (60)Co γ-ray irradiation was carried out to highlight (211)At-MABG-specific gene expression. For comparisons, 10% and 80% iso-survival doses (0.8 and 0.1 kBq/mL for (211)At-MABG and 10 and 1 Gy for (60)Co γ-rays) were used. Results: Enrichment analysis of differentially expressed genes (DEGs) and analysis of the gene expression profiles of cell cycle checkpoints revealed similar modes of cell death via the p53-p21 signaling pathway after (211)At-MABG treatment and γ-ray irradiation. The top list of ranked DEGs demonstrated the expression of key genes on the decrease in the survival following (211)At-MABG exposure, and four potential genes (Mien1, Otub1, Vdac1 and Vegfa genes) of (211)At-MABG therapy. Western blot analysis indicated increased expression of TSPO in (211)At-MABG-treated cells, suggesting its potential as a PET imaging probe. Conclusion: Comprehensive RNA-seq revealed contrasting cellular responses to γ-ray and α-particle therapy, leading to the identification of four potential candidate genes that may serve as molecular imaging and (211)At-MABG therapy targets.